Hepatic Subcapsular Hematoma: Two Neonates With Disparate Presentations - Maliyackel Aiyappanpillai Anjay; Chaniyil Krishnan Sasidharan; Parameswaran Anoop (Elsevier, 2012)
Subcapsular hematoma of the liver rarely occurs in neonates and the diagnosis is often missed or delayed. We report two babies who had this uncommon condition in the early neonatal period. In the first baby, the hematoma was associated with ventouse delivery and presented with abdominal distension and worsening jaundice. In contrast, the other baby was relatively well, with progressive pallor as the only clinical finding. The former had no other identifiable risk factors, whereas the latter was confirmed as having classical hemophilia. The literature is briefly reviewed with regards to incidence, etiology, diagnosis and management. Awareness of this unusual entity coupled with a high index of suspicion is essential for early identification and stabilization of such babies.